Transfer of dietary allergen in human milk - Aryono Harsono; Anang Endaryanto (Paediatrica Indonesiana, 1999)
The presence of dietary allergens in breast milk have been studied eitherin animal model or human milk. Transfer of these allergens to the infants have been proven qualitatively and quantitatively. Maternal dietary allergen transfer can also be detected by the presence of antibody response in the infants. The relationship of maternal dietary allergens and sensitisation to the infants can be observed in prolonged breastfed infants. The benefit of maternal dietary avoidance may be found either early from the beginning of pregnancy or in the lactation period. Factors predicting the onset of atopic disease are the nature of dietary protein in breast milk, lgA in breast milk, family history of atopy, allergen exposure, cord blood IgE and contributory factors. Evaluation of infants with sensitivity to dietary allergen in breast milk mainly is DBPCFC. Preventive measure is still avoidance of maternal dietaryÂ  allergen. The mainstay of treatment is avoidance of the offending foods obtained from food challenge.